1998
DOI: 10.1300/j069v17n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Major Depression

Abstract: The authors review recent literature that has demonstrated an association between cigarette smoking behavior and major depression. Persons with major depression are more likely to smoke and to have difficulty when they try to stop. When they manage to succeed in stopping, such persons are at increased risk of experiencing mild to severe states of depression, including full blown major depression. The period of vulnerability to a new depressive episode appears to vary from a few weeks to several months after ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
2
12

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(145 citation statements)
references
References 21 publications
10
121
2
12
Order By: Relevance
“…In accordance with other epidemiological reports (20,21,22) , women with smoking habits had higher prevalence of depressive mood (62%) and feeling of fatigue (71%). We also found that cigarette smoking was an independent risk factor for psychological symptoms.…”
Section: Smoking Habitssupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with other epidemiological reports (20,21,22) , women with smoking habits had higher prevalence of depressive mood (62%) and feeling of fatigue (71%). We also found that cigarette smoking was an independent risk factor for psychological symptoms.…”
Section: Smoking Habitssupporting
confidence: 92%
“…Therefore, it is possible that women with emotional problems may attempt to self-treat mood disorders by smoking. On the other hand, withdrawal of nicotine may in turn cause or worsen psychological problems, in particularly in the women with previous depression episodes (22) .…”
Section: Smoking Habitsmentioning
confidence: 99%
“…The present data suggest that reduced serotonergic neurotransmission may be one of the neurobiological abnormalities underlying the symptom of "diminished interest or pleasure" seen in both amphetamine and nicotine withdrawal in humans (American Psychiatric Association 1994; Covey et al 1998;Glassman 1993;Hughes 1992;Markou et al 1998). This hypothesis is consistent with the observation that withdrawal from other drugs of abuse, such as cocaine (Parsons et al 1995) or ethanol (Weiss et al 1996), also is characterized by decreased serotonergic neurotransmission as reflected in decreased in vivo dialysate serotonin levels.…”
Section: Discussionmentioning
confidence: 74%
“…
Cessation of chronic nicotine or amphetamine administration precipitates withdrawal syndromes characterized by affective symptoms, including "diminished interest or pleasure" in rewarding stimuli (i.e., anhedonia) (American Psychiatric Association 1994;Covey et al 1998;Glassman 1993;Hughes 1992). Interestingly, the symptom of "diminished interest or pleasure" is not only a symptom of drug withdrawal, but also a core symptom of depression and a negative symptom of schizophrenia (American Psychiatric Association 1994;Markou et al 1998).
…”
mentioning
confidence: 99%
“…34,55 The self-medication hypothesis has a stronger evidence base in major depression (table 1). 56 Similarly, the other hypotheses also require stronger longitudinal and biological evidence to assess their validity. These three hypotheses have different implications for policies to reduce cigarette smoking in people with serious mental illness.…”
Section: Smoking In Serious Mental Illness: Cause or Effect?mentioning
confidence: 99%